Analiza razlik v sistemih ravnanja z ljudmi pri delu v košarkarskih klubih Jugovzhodne Evrope - Ivašković, Igor (Šport (Ljubljana), 2018)
The paper presents the specificities of basketball clubs from selected transition countries of South East Europe. The author analyzes the differences between clubs at different quality levels regarding the financing, the level of professionalization, the personnel structure, the influence on the HRM strategy and the role of the coach in HRM processes. The results show that: 1) the higher quality clubs have larger financial budgets, obtain higher percentage of the latter form private sources, and have better infrastructure; 2) clubs that play in the first national leagues have a larger administration and are predominantly professionalized organizations, while the second and third division clubs operate on an amateur level; 3) the greatest responsibility for the success is on coaches, athletes and clubs' presidents; 4) in the field of HRM the competences and influence of the sports directors increases, while the influence of the clubs' presidents decreases with the level of quality; 5) the influence of sponsors' representatives and agent also increases with the level of quality.
Keywords: Jugovzhodna Evropa; kadrovski management; košarka; RLD; šport; športni klubi; zaposleni